Metabolic syndrome in Turkish children and adolescents - (:unkn) unknown (W B SAUNDERS CO-ELSEVIER INC, 2006)
The aim of this study was to determine the prevalence and phenotype of metabolic syndrome in Turkish children and adolescents. We adapted the National Cholesterol Education Program Adult Treatment Panel III criteria of metabolic syndrome to children and adolescents. Using the international cutoff points and percentiles, we determined 10- to 17-year-old Turkish children and adolescents with high blood pressure, high triglyceride (TG), low high-density lipoprotein cholesterol (HDL-C), fasting glucose of 100 mg/dL or greater, and elevated body mass index corresponding to overweight or obesity. We examined 1385 apparently healthy students between the ages of 10 to 17 years from Ankara, Turkey: 4.9% of the subjects were overweight or obese; 29.2% had either low HDL-C and/or high TG levels; and 15.7% had either systolic or diastolic blood pressure above the 95th age-, sex-, and height-specific percentile. Thirty students (2.2%) had metabolic syndrome by having 3 or more risk variables. Metabolic syndrome was nearly 10 times more common among overweight and obese students (21%), compared with lean students. Components of metabolic syndrome such as high blood pressure and high TG, and low HDL-C levels were common among Turkish children and adolescents. Strategies should focus on early detection and treatment of these risk variables in Turkish children. (c) 2006 Elsevier Inc. All rights reserved.
Keywords: OBESITY; CHOLESTEROL; OVERWEIGHT; CHILDHOOD; LIPOPROTEINS; DEFINITION; PREVALENCE; NUTRITION; BOGALUSA; LIPIDS